Quantification of standardised uptake value for ¹⁸F-FDG positron emission tomography in Malaysia - Hanafi, Muhammad Hafiz (2017)
The role of Positron Emission Tomography/Computed Tomography (PET/CT) modalities is becoming more important concomitantly with the increase of oncology cases in Malaysia. Thus, it is the perfect time to perform a study to standardise the PET/CT image quality in Malaysia. This study aimed to compare the quantification of image quality of PET/CT with a standardised uptake value (SUV) parameter. In general, this study was carried out with the purpose of identifying the standardisation of quantification of standardised uptake value, SUVcontrolled for 18F-FDG PET between two independent PET modalities at two different institutions. The analysis was done on the SUVcontrolled of technical techniques (PET phantom) as a control standard for the validation of the PET-CT images of selected subjects with Fasting Blood Glucose index as the adjusted index to synchronise the two independent data sets. It was found that the SUVcontrolled was a potential conversion marker to validate the in vivo standardisation techniques for the two independent PET/CT modality systems based on the reference standard of the matched FBS and the in vitro 18F-FDG phantom. This study confirmed that the two independent PET modalities at paired-centre could potentially be standardised on the independent image quality based on the SUVmax quantification as the two independent measured were insignificantly different.